2021
DOI: 10.1038/s41598-021-99841-5
|View full text |Cite
|
Sign up to set email alerts
|

Light-driven oxygen evolution from water oxidation with immobilised TiO2 engineered for high performance

Abstract: Calcination treatments in the range of 500–900 °C of TiO2 synthesised by the sol–gel resulted in materials with variable physicochemical (i.e., optical, specific surface area, crystallite size and crystalline phase) and morphological properties. The photocatalytic performance of the prepared materials was evaluated in the oxygen evolution reaction (OER) following UV-LED irradiation of aqueous solutions containing iron ions as sacrificial electron acceptors. The highest activity for water oxidation was obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…As the Pd-loaded increased, the average crystallite size decreased, and the surface area increased. These results also agree with Sampaio et al [36] X-ray photoelectron spectroscopy of pure ZnO and 5 wt % Pd-ZnO NPs is presented in Figure 5. The XPS survey spectra (Figure 5a) of pure ZnO and 5% Pd-ZnO show the prominent characteristic peaks of Zn2p, O 1s, and C 1s with their given atomic ratios in Table 2.The high-resolution XPS spectra (HR-XPS) of both pure ZnO and 5% Pd-ZnO (Figure 5b) show two characteristic peaks for Zn2p, which are assigned to Zn 2p 1/2 and Zn 2p 3/2 at BE 1045.31 and 1022.31 eV in pure ZnO and 1044.24 and 1021.25 eV in 5% Pd-ZnO.…”
Section: Surface Area and Xps Analysessupporting
confidence: 92%
See 1 more Smart Citation
“…As the Pd-loaded increased, the average crystallite size decreased, and the surface area increased. These results also agree with Sampaio et al [36] X-ray photoelectron spectroscopy of pure ZnO and 5 wt % Pd-ZnO NPs is presented in Figure 5. The XPS survey spectra (Figure 5a) of pure ZnO and 5% Pd-ZnO show the prominent characteristic peaks of Zn2p, O 1s, and C 1s with their given atomic ratios in Table 2.The high-resolution XPS spectra (HR-XPS) of both pure ZnO and 5% Pd-ZnO (Figure 5b) show two characteristic peaks for Zn2p, which are assigned to Zn 2p 1/2 and Zn 2p 3/2 at BE 1045.31 and 1022.31 eV in pure ZnO and 1044.24 and 1021.25 eV in 5% Pd-ZnO.…”
Section: Surface Area and Xps Analysessupporting
confidence: 92%
“…The XPS survey spectra (Figure 5a) of pure ZnO and 5% Pd-ZnO show the prominent characteristic peaks of Zn2p, O 1s, and C 1s with their given atomic ratios in Table 2.The high-resolution XPS spectra (HR-XPS) of both pure ZnO and 5% Pd-ZnO (Figure 5b) show two characteristic peaks for Zn2p, which are assigned to Zn 2p 1/2 and Zn 2p 3/2 at BE 1045.31 and 1022.31 eV in pure ZnO and 1044.24 and 1021.25 eV in 5% Pd-ZnO. [34,35] This reveals The HR-XPS spectra of both pure ZnO and 5% Pd-ZnO show two characteristic peaks for O 1s (Figure 5c,d), which are assigned to the lattice oxygen (O L) and the chemisorbed surface oxygen (O C ) either in the form of oxygen vacancies or hydroxyl oxygen, [36] respectively. The BE of O L and O C are located at BE = 532.94 and 531.24 eV in the pure sample and BE = 530.92 eV and 529.91 eV in the Pd-ZnO sample (Figure 4c,d).…”
Section: Surface Area and Xps Analysesmentioning
confidence: 90%
“…This is supported by an almost linear H 2 evolution in the presence of a hole scavenging agent in figure 4(a) (i.e. methanol oxidation competes with the formation of peroxo-species), and also by the lack of observable O 2 evolution (monitored in the gas phase by GC) in NS samples (as widely reported in the literature) [30,70,71]. In line with observations for NS, conventional anodic TiO 2 nanotubes similarly show only a short period of O 2 production (during the initial 1 h) followed by its complete suppression (figure S10), while a further O 2 consumption in the reaction medium suggests H 2 O 2 production via two-electron reduction of the produced O 2 [64][65][66].…”
Section: Resultssupporting
confidence: 77%
“…(iv) Optical absorption should be high in the visible region . Moreover, Fujisima et al have reported the photoelectrocatalytic WS for the first time by employing TiO 2 as a photocatalyst. Later on, several semiconductor materials are investigated for the enhancement of photocatalytic activity. Among them, three-dimensional (3D) semiconductor photocatalysts, specifically metal oxides, are widely explored in hydrogen generation. However, their wide bandgap produces poor optical absorption, as they only absorb the UV light from the solar spectrum .…”
Section: Introductionmentioning
confidence: 99%